ANALISIS PROSES MUTASI PROMOSI JABATAN PEGAWAI NEGERI SIPIL DI KANTOR BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA (BKPSDM) KOTA PALEMBANG - Holipah Holipah; Helda Fitriani; Asmawati Asmawati; Yofitri Heny Wahyuli (Jurnal STIA Bengkulu, 2023)
The most prominent employee mutation activity in Palembang City is in the context of promotion and transfer in order to evenly distribute employees in the ranks of the Office, Agency and Office in Palembang City. The type of research that is considered appropriate in this study is a descriptive method with a qualitative approach. The data collection of this research was carried out based on observations, interviews and documents. The data analysis technique used in this study is a taxonomic analysis technique, which is to form a detailed and in-depth analysis in discussing a theme or subject matter. This taxonomic analysis is used to describe in detail the process of mutation of promotions for civil servants at the Office of the Personnel and Human Resources Development Agency of Palembang City. Based on the research results, in terms of mutation of civil servants, the authority that exists in the government is very broad. Only the appointment of echelon II requires approval from the top level government, and the appointment of the Regional Secretary requires approval from the local DPRD. The procedure for employee transfers differs according to the position of the mutation. For mutation due to promotion, it has been determined based on the applicable legislation.